Distribuição da umidade do solo no cultivo da goiabeira sob altas frequências de irrigação e diferentes coberturas mortas - Albuquerque, André Henrique Pinheiro (2015)
Fruit production has been shown as an alternative to the development of semiarid region. However, some studies should be implemented in relation to guava cultivation in Ceará, developed mainly in excessively sandy soils, such as those prevailing in Tabuleiros de Russas. Thus, the experiment was to evaluate the effects of high frequency of irrigation and the use of mulches on water retention in the root zone of guava and its yield over two cycles. The experimental design was a randomized block with split plots and four replications. In the treatments the time of daily irrigation was fractionated into five different amounts of "pulses", into different fractions of the total time interval. Already in the subplot examined the effects of absence and presence of four different mulches. The analyzed variables were: water tension in the soil, spatial distribution of soil moisture, number of fruits, average fruit weight, yield, diameter, size and circumference of the fruit, density, shell thickness and diameter of pulp. Initially, data were submitted to analysis of variance and data with significance by the F test, were subjected to regression analysis. There wasn’t significant interaction for the water tension in the soil during the first cycle, while the opposite occurred in the second cycle due to higher demand for water by culture. The spatial distribution of soil moisture showed that the highest values of this variable were found when it divided the daily irrigation depth in the largest quantities of pulses. The use by the producer of larger amounts of irrigation pulses gives you better answers for the guava yield characteristics. Your use of mulch producer on the soil surface provides benefits as water retention in the layers near to the surface. It is recommended that producers of the Distrito de Irrigação Tabuleiros de Russas, and the areas with sandy soils, the division of daily water depth in a lot of pulses and the conduct of crops with soil cover, as banana’s crop waste.